2022
DOI: 10.3390/ijerph19031502
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Sociodemographic Factors Associated with Overweight and Obesity among Adults in Poland: A 2019/2020 Nationwide Cross-Sectional Survey

Abstract: Detailed characteristics of the weight status of the population is necessary for the effective prevention of health disorders, e.g., through personalized nutrition education. This study aimed to characterize weight status and identify sociodemographic factors associated with overweight/obesity in a representative sample of adult inhabitants of Poland. This cross-sectional study was carried out from July 2019 to February 2020 on a representative nationwide sample of individuals aged 18+ in Poland. The study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 40 publications
0
16
2
Order By: Relevance
“…Despite the importance of the food industry in the Polish economy, a markable percentage of adults in Poland present a moderate or low level of knowledge about food, nutrition, and their relation to health [ 12 , 26 ]. Moreover, the prevalence of overweight or obesity in Poland is one of the highest in the EU [ 27 , 28 ]. Rapid socioeconomic changes observed in recent decades have affected the lifestyle of Poles, including dietary behaviors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of the food industry in the Polish economy, a markable percentage of adults in Poland present a moderate or low level of knowledge about food, nutrition, and their relation to health [ 12 , 26 ]. Moreover, the prevalence of overweight or obesity in Poland is one of the highest in the EU [ 27 , 28 ]. Rapid socioeconomic changes observed in recent decades have affected the lifestyle of Poles, including dietary behaviors [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most populations, the prevalence of obesity in adults is greater for women than for men [ 43 ]. However, national data showed that in Poland, the prevalence of overweight or obesity is higher among men (68.9% vs. 48.2%) [ 44 ]. In this study, the hospitalization rate due to type 2 diabetes was higher among men, which may result from the sex differences in the prevalence of overweight/obesity in Poland [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, national data showed that in Poland, the prevalence of overweight or obesity is higher among men (68.9% vs. 48.2%) [ 44 ]. In this study, the hospitalization rate due to type 2 diabetes was higher among men, which may result from the sex differences in the prevalence of overweight/obesity in Poland [ 44 ]. The hospitalization rate due to type 2 diabetes increases with the age.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate the association between FTO gene in rs17817449 and the risk of obesity, arterial hypertension, diabetes mellitus, www.journals.viamedica.pl/medical_research_journal and coronary artery disease in Upper Silesian population. Obesity is considered to be one of the most prevalent health problems which affects 18% of adult women and 20% of adult men in Poland [9]. It is closely related to other civilization diseases including insulin resistance, type 2 diabetes mellitus, arterial hypertension, and coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%